Consumption of sugar-rich food products among Brazilian students:National School Health Survey (PeNSE 2012) - Nathália Luíza Ferreira; Rafael Moreira Claro; Aline Cristine Souza Lopes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract This study aimed to analyze the consumption of high-sugar foods by Brazilian schoolchildren and to identify associated factors, based on data from the National School Health Survey (PeNSE 2012). Consumption of these foods was classified as: do not consume sweets and soft drinks regularly; consume sweets or soft drinks regularly; and consume sweets and soft drinks regularly. Its association with sociodemographic information, eating habits, and family contexts were investigated via multiple ordinal regressions. Regular consumption of sweets and/or soft drinks was reported by 19.2% and 36.1% of adolescents, respectively, and higher prevalence was associated with female gender, age 14-15 years, higher maternal education, not living with the mother and father, not eating meals with the parents, eating while watching TV, and longer TV time. Nearly one-fifth of adolescents regularly consumed sweets and soft drinks, which was associated with socio-demographic and behavioral factors that should be targeted in order to improve their food consumption.